The Importance of Global Effort to Secure Space Sector from Cyberattack - Antonia Rahayu Rosaria Wibowo (Intermestic: Journal of International Studies, 2022)
The use of internet has grown massively since 1990s. It has brought both life improvement and criminal activities in cyberspace. The cyberattack has affected most sectors including space sector. The space sector is vulnerable to cyberattacks because a lot of human technologies depend on it. The actors behind it cannot be identified as an individual based on geographical location, so that, global effort is needed. The importance of global effort to secure space sector from cyberattacks is discussed in this paper. This paper used the descriptive method and library research techniques to collect data. Data about cyberattack on space sector and efforts to secure them were collected from academic journals and international organizations’ documents. Then, they were analyzed using the global governance theory. The result shows that global effort to secure space sector from cyberattack is important because it is a transnational problem, furthermore space sector connects modern infrastructures worldwide.